Anatomically Conformable, Three-Dimensional, Detachable Platinum Microcoil System for the Treatment of Intracranial Aneurysms - Niemann, David; Aviv, Richard; Cowsill, Caroline; Sneade, Mary; Molyneux, Andrew J. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: The configurations of detachable platinum coils have evolved over the last decade. Our objective was to assess the efficacy of the anatomically conformable three-dimensional (ACT) detachable platinum microcoil in the treatment of intracranial aneurysms.METHODS: A series of 141 patients presented between May 2000 and August 2002 to a single neurointerventionalist for endovascular treatment of intracranial aneurysms. Eight patients were treated at another institute or are now overseas. The remaining 133 patients had 141 aneurysms, which were treated; 110 were ruptured and 31 were unruptured. The clinical conditions and aneurysm locations were recorded. The procedural technique was the same as that used with the Guglielmi detachable coil (GDC) device, though the coil detachment mechanism was unique. The ACT microcoil was used in almost all cases as the initial coil.RESULTS: Complete (100%) occlusion was achieved in 104 (74%) aneurysms. Thirty four (24%) had subtotal occlusion (≥95%), and three (2%) had incomplete occlusion (<95%). The ACT coil conformed to both spherical and irregularly shaped aneurysms. No procedure-related deaths occurred, and there was no aneurysm rupture related to coil deployment. No postprocedural rebleeding was observed.CONCLUSION: The ACT microcoil device is feasible as an alternative platinum coil device, offering some advantages over other currently available devices.